315A new strategy for teaching Epidemiology in Public Health Education: Hybrid Team Based Learning-Personalised Education. (2nd September 2021) - Ha, Tam; Kemp, Byron; Wallace, Margaret
Abstract: Focus of Presentation: Hybrid Team Based Learning and Personalised Education (HTBL-PE) is an unique student-centred teaching strategy used to teach epidemiology in the Bachelors of Public Health at the University of Wollongong. It aims to systematically build abilities in epidemiology; strengthen self-confidence and belief, by teaching the way students learn and harnessing team's capabilities to strengthen the individual. Findings: 73 out of 84 students enrolled in Spring 2019, completed surveys at the beginning and end of semester (87%). At the end of semester, the vast majority of students indicated their interest in epidemiology increased (93%), critical thinking had improved (92%), and their confidence as independent learners had increased (86%). More than two thirds of the students had already applied learnings from this subject in other settings (67%). In general, these outcomes did not differ significantly by gender or across learning styles. Students' final mark for this subject was significantly higher than their Weighted Average Mark (WAM) prior to the semester (+17.4, p < 0.001). Mean scores were >84/100 overall for the subject (<0.5% failure rate). Conclusions: HTBL-PE is a new, innovative teaching strategy with low failure rates and high mean scores. Successful attainment of learning outcomes did not differ across gender or learnings styles. Key messages: HTBL-PE is an effective teaching strategy with positive student outcomes. It caters to a variety of students and learning styles with evidence students have applied these techniques to other learning settings.